Assessment of nitric oxide (NO) redox reactions contribution to nitrous oxide (N2O) formation during nitrification using a multispecies metabolic network model. Issue 5 (26th November 2015) - Perez‐Garcia, Octavio; Chandran, Kartik; Villas‐Boas, Silas G.; Singhal, Naresh
ABSTRACT: Over the coming decades nitrous oxide (N2 O) is expected to become a dominant greenhouse gas and atmospheric ozone depleting substance. In wastewater treatment systems, N2 O is majorly produced by nitrifying microbes through biochemical reduction of nitrite (NO2 − ) and nitric oxide (NO). However it is unknown if the amount of N2 O formed is affected by alternative NO redox reactions catalyzed by oxidative nitrite oxidoreductase (NirK), cytochromes (i.e., P460 [CytP460 ] and 554 [Cyt554 ]) and flavohemoglobins (Hmp) in ammonia‐ and nitrite‐oxidizing bacteria (AOB and NOB, respectively). In this study, a mathematical model is developed to assess how N2 O formation is affected by such alternative nitrogen redox transformations. The developed multispecies metabolic network model captures the nitrogen respiratory pathways inferred from genomes of eight AOB and NOB species. The performance of model variants, obtained as different combinations of active NO redox reactions, was assessed against nine experimental datasets for nitrifying cultures producing N2 O at different concentration of electron donor and acceptor. Model predicted metabolic fluxes show that only variants that included NO oxidation to NO2 − by CytP460 and Hmp in AOB gave statistically similar estimates to observed production rates of N2 O, NO, NO2 − and nitrate (NO3 − ), together with fractions of AOB and NOB species in biomass. Simulations showed that NO oxidation to NO2 − decreased N2 O formation by 60% without changing culture's NO2 − production rate. Model variants including NO reduction to N2 O by Cyt554 and cNor in NOB did not improve the accuracy of experimental datasets estimates, suggesting null N2 O production by NOB during nitrification. Finally, the analysis shows that in nitrifying cultures transitioning from dissolved oxygen levels above 3.8 ± 0.38 to <1.5 ± 0.8 mg/L, NOB cells can oxidize the NO produced by AOB through reactions catalyzed by oxidative NirK. Biotechnol. Bioeng. 2016;113: 1124–1136. © 2015 Wiley Periodicals, Inc. Abstract : An original multi‐species metabolic network model for nitrifying microbial communities is shown. The model simulated nitrous oxide (N2 O) production rates observed during ammonia oxidation to nitrite and nitrate. Analysis of the modeled fits to data from nine published experimental studies shows that NO oxidation limits the amount of N2 O formed during nitrification by mixed cultures.